INTERPERSONAL MEANINGS OF MODALITY IN JACINDA ARDERN’S SPEECHES ON COVID-19 - Evelina Ayu Kristianti (English Department of Faculty of Tarbiyah and Teacher Training, 2020)
Systemic Functional Linguistics (SFL) is a theory which analyses the language function to understand the meanings and purposes of language in written text or speech. In this research, SFL is employed to discover the interpersonal meanings on Jacinda Ardern’s speeches on COVID-19, seen from the modality since it is one of the most important elements in SFL which shows the speaker’s attitudes. This research uses Jacinda Ardern’s speeches on 20 April 2020 and 15 July 2020. Halliday’s modal category is used as the theoretical framework; thus, the interpretation will derive from his theory. This research also employs discourse analysis as the approach in order to understand the relation between language elements and social context in meaning-making. This study had different implementation of modal category from what Halliday had proposed which is triggered by the social situation during pandemic in New Zealand. This research discovers that the first speech only uses two types of modality which are probability and obligation, meanwhile the second speech uses all types of modality. The difference between the first and the second speech is due to the different circumstances. However, in general, the interpersonal meanings represented from the modality in the speeches are the commitment, empathy, dan quick respond of the speaker. Keywords- interpersonal meanings, modality, speech, Jacinda Ardern’s speech, COVID-19